2020
DOI: 10.1101/2020.10.22.350801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Gut Microbial Peptide and Molecular Mimicry in the Pathogenesis of Type 1 Diabetes

Abstract: Type 1 Diabetes (T1D) is an autoimmune disease characterized by destruction of pancreatic β-cells. Focusing on the main insulin epitope, insulin B-chain 9-23 (insB:9-23), we explored whether a microbial insB:9-23 mimic could modulate T1D. We now demonstrate that a microbial insB:9-23 mimic of Parabacteroides distasonis, a human gut commensal, exclusively stimulates non-obese diabetic (NOD) mouse T cells specific to insB:9-23. Indeed, immunization of NOD mice with either the bacterial mimic peptide or insB:9-23… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 112 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…Table 2 summarizes the results of searching for molecular mimicry in the analyzed genomes to identify the presence of insulin B chain insB:9–23 peptide mimics (SHLVEALYLVCGERG) [ 48 ], and the two microbial altered peptide ligands (MVWGPDPLYV and RQFGPDWIVA) from the natural preproinsulin (ALWGPDPAAA) [ 50 ]. A variant of the insB:9–23 peptide (HL L EALY MTY GE) was identified only in the genome of B. uniformis PtF Sb3P5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 summarizes the results of searching for molecular mimicry in the analyzed genomes to identify the presence of insulin B chain insB:9–23 peptide mimics (SHLVEALYLVCGERG) [ 48 ], and the two microbial altered peptide ligands (MVWGPDPLYV and RQFGPDWIVA) from the natural preproinsulin (ALWGPDPAAA) [ 50 ]. A variant of the insB:9–23 peptide (HL L EALY MTY GE) was identified only in the genome of B. uniformis PtF Sb3P5.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Falony et al [ 62 ] found an increase in Parabacteroides in individuals with low microbiome diversity that exhibited a preference for white, low fiber bread, and predominance of recent amoxicillin treatment. The recent reported molecular mimics of the human insulin B:9–23 peptide in P. distasonis 33B (from the human gut microbiome) [ 48 ] is an important warning for hidden autoimmune triggers. The genome of P. distasonis PtFD14MH1 did not show the presence of any variant of insB:9–23, however a variant of the Human Natural preproinsulin AWL, that is very similar to a previously described variant in C. asparagiforme, was identified [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a local BlastP library, we searched for the presence of peptide sequences with high sequence similarity to 62 human peptide hormones and regulatory proteins (88). We identified viral sequences that showed significant similarity with 16 different human peptide hormones, including insulin, insulin-like growth factors 1 and 2 (IGF-1 and IGF-2), tumor necrosis factor, endothelin-1 and -2, interleukin 6, and adiponectin (88,89). Until we discovered viral hormones, viral mimicry examples were limited to immunomodulatory proteins and growth factors (90)(91)(92)(93)(94)(95).…”
Section: A Novel Mechanism To Manipulate Host Metabolism: Discovery Of Viral Insulin and Insulin-like Growth Factor-like Peptidesmentioning
confidence: 99%